Gambaran Pengetahuan Sikap dan Tindakan Terhadap STBM Pilar Pertama Stop BABS di Desa Haya Kecamatan Tehoru Kabupaten Maluku Tengah - Baharudin Layn (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The background of this study is the practice of open defecation (OD), which is a public health problem. OD refers to the act of disposing of feces in open areas such as rice fields, fields, bushes, rivers, and beaches, which can pollute the environment, soil, air, and water. This study aims to determine the knowledge, attitudes, and practices of the community in RT 05 Haya Village, Tehoru District, Central Maluku Regency regarding stopping ODD. This study used a descriptive method, with a sample of 40 families selected through a random sampling technique. Data were collected using a questionnaire. The results showed that most people had quite good knowledge about ODD, with 50% of respondents in the quite good category. Community attitudes were also quite good, with 70% of respondents showing a positive attitude towards stopping ODD. However, community actions were still less good, with 42.5% of respondents showing less good actions regarding ODD. The conclusion of this study is that although the knowledge and attitudes of the community in Haya Village were quite good, their actions were still lacking. Therefore, cooperation is needed between the village government, Tehoru Health Center, and community leaders to regularly hold outreach regarding BABS.